2009
DOI: 10.1007/s12272-009-2018-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimyristoylphosphatidylethanol and ethanol on thickness of neuronal membrane lipid bilayers

Abstract: The aim of this study was to provide a basis for examining the molecular mechanism for the pharmacological action of ethanol. Energy transfer between the surface fluorescent probe 1-anilinonaphthalene-8-sulfonic acid and hydrophobic fluorescent probe 1,3-di(1-pyrenyl)propane was used to examine the effect of both dimyristoylphosphatidylethanol (DMPEt) and ethanol on the thickness (D) of the synaptosomal plasma membrane vesicles (SPMV) isolated from the bovine cerebral cortex. The thickness (D) of the intact SP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2011
2011
2011
2011

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(16 reference statements)
1
0
0
1
Order By: Relevance
“…In the current study, ethanol decreased ACh-induced contractions in rabbit duodenum and this accords with other studies in which ethanol has been shown to reduce the contractions produced by ACh in isolated rat ileum (32), in canine jejunal circular smooth muscle (8) and in rabbit duodenum (13). Furthermore, ethanol decreased the thickness of synaptosomal plasma membrane vesicles lipid bilayer (33).…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, ethanol decreased ACh-induced contractions in rabbit duodenum and this accords with other studies in which ethanol has been shown to reduce the contractions produced by ACh in isolated rat ileum (32), in canine jejunal circular smooth muscle (8) and in rabbit duodenum (13). Furthermore, ethanol decreased the thickness of synaptosomal plasma membrane vesicles lipid bilayer (33).…”
Section: Discussionsupporting
confidence: 92%
“…Uma provável explicação para este fato seria a capacidade demonstrada do DMSO induzir a translocação de moléculas de lipídeos e sua re-distribuição entre as faces externa e interna da membrana celular, em evento conhecido como flip-flop, causando uma diminuição da espessura da membrana celular e mudança na carga iônica dos lipídeos da superfície da mesma (GURTOVENKO et al, 2008). De modo similar, dados da literatura demonstraram que o etanol causa uma diminuição na espessura da membrana celular, também, por alterações na posição dos lipídeos na bicamada dessas membranas (PARK et al, 2009). A partir dessas informações, podemos sugerir que a posição e/ou as cargas iônicas dos lipídeos de superfície da membrana celular seja um aspecto importante para a interação da PA-BJ com as CEs e, conseqüentemente, para o desencadeamento de sua ação sobre as mesmas.…”
Section: Efeitos Do Compostounclassified